Organic Matter Dynamics in a Tropical Gallery Forest in a Grassland Landscape - Rezende, Renan S.; Graça, Manuel Augusto Simões; Santos, Anderson M. dos; Medeiros, Adriana Oliveira; Santos, Paola F.; Nunes, Yule Roberta Ferreira; Gonçalves, José Francisco Júnior (Biotropica, 2016)
The high biodiversity of tropical forest streams depends on the strong input of organic matter, yet the leaf litter decomposition dynamics in these streams are not well understood. We assessed how seasonal litterfall affects leaf litter breakdown, density and biomass of aquatic invertebrates, and the microbial biomass and sporulation of aquatic hyphomycetes in a South American grassland 'vereda' landscape. Although litter production in the riparian area was low, leaf litter breakdown was high compared with other South American systems, with maximum values coinciding with the rainy season. Fungal biomass in decomposing leaves was high, but spore densities in water and sporulation rates were very low. Invertebrates were not abundant in litter bags, suggesting they play a minor role in leaf litter decomposition. Chironomids accounted for ~70 percent of all invertebrates; only 10 percent of non-Chironomidae invertebrates were shredders. Therefore, fungi appear to be the drivers of leaf litter decomposition. Our results show that despite low productivity and relatively fast litter decomposition, organic matter accumulated in the stream and riparian area. This pattern was attributed to the wet/dry cycles in which leaves falling in the flat riparian zone remain undecomposed (during the dry period) and are massively transported to the riverbed (rainy season). © 2016 The Association for Tropical Biology and Conservation.
Keywords: Aquatic Organism; Biodiversity; Biomass; Decomposition; Equipment; Fungus; Grassland; Landscape Structure; Leaf Litter; Litterfall; Organic Matter; Pavement; Riparian Zone; Soil Biota; Sporulation; Streamwater; Tropical Forest; South America; Chironomidae; Fungi; Hyphomycetes; Invertebrata